THE IMPLEMENTATION OF FLASH CARDS TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Dian Farida; Hasna Dian Isrina; Yanuarti Apsari (IKIP Siliwangi, 2019)
This research is a classroom action research. The objective of this research is to investigate the process of improving students’ vocabulary mastery by using flash cards. The respondents in this research was seventh grade students of MTs Nurul Islam. There are 30 students. In collecting data, this research used interviews, observation, and tests. The researchers assessed four aspects of vocabulary in determining students’ scores.This research employed two cycles in this research and perform in four stage, namely; planning, acting, observing, and reflecting. The results of the research showed that the implementation of flash cards can increase students' vocabulary. It can be seen from the development in the mean score of students: for aspect meaning at pretest cycle 1 is 63 and in post test in cycle 2 is 78, for spelling aspects at pretest cycle 1 is 58 and in post test in cycle 2 is 81, for pronunciation aspects at pretest cycle 1 is 65 and in post test in cycle 2 is 83, and for aspects of word use at pretest cycle 1 is 71 and in post test in cycle 2 is 88.